Manitoba First Nations Casino Project Selection Committee : report and recommendations ... - Manitoba First Nations Casino Project Selection Committee (Manitoba First Nations Casino Project, 2000)
The First Nations Casino Project Selection Committee had the mandate to select up to five First Nations gaming facilities proposed for establishment in Manitoba, based on their ability to fulfill such objectives as providing benefits to First Nations, promoting economic development & tourism, and creating jobs. This report reviews the work of the Committee, provides background on the Casino Project and on the content requirements of casino proposals, and summarizes the Committee's assessment process & evaluation criteria. The report concludes with recommendations regarding the establishment of five casinos, with brief descriptions of each accepted proposal, and discussion of the factors necessary for the success of the Casino Project. ...